Maternal influence on early lipid content in an introduced partially anadromous population of Oncorhynchus mykiss - Ana L. Liberoff; Alejandra A. Leal; María E. Díaz De Vivar; Carla M. Riva‐Rossi; Miguel A. Pascual (Journal of Fish Biology, 2019)
This study evaluated how the maternal migratory tactic in a partially anadromous population of Oncorhynchus mykiss may influence the early energetic status of their offspring. Total lipid content variation (% dry mass) of recently emerged fry caught in the Santa Cruz River, Argentina, was evaluated as a function of their maternal origin (anadromous v . resident) and fork length ( L F ). Lipid content of fry decreased with L F and was higher for offspring of anadromous mothers.